A SIMPLE MODEL USED IN SOFTWARE QUALITY EVALUATION FOR THE ECONOMIC APPLICATIONS - Anamaria Siclovan (Studies and Scientific Researches: Economics Edition, 2014)
It was noted that, over the time, in the field of economic informatics and economy, most people have become dependent on software applications. Do economic applications reach a high threshold of quality such as to satisfy the customers who are dependent on them? This study proposes to present a model that analyzes the quality of economic applications. By applying this model, we could tell if an economic application which is submitted to the analysis reach a certain quality threshold or not. Thus, by analyzing the factors and sub-factors that characterize any economic application, we can analyze the software quality.